2021
DOI: 10.26529/cepsj.1062
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Informed Educational Practice in Catalan Education: From Public Agenda to Teachers’ Practice

Abstract: Catalonia has a long tradition of school innovation movements. These have increased in recent years as public administration and private entities have initiated substantial school reforms oriented toward the use of evidence in teaching practice. As the Catalan education system is highly autonomous, not all schools have embraced the evidence-informed practice (EIP) movement, and this has created differences between schools that choose to implement a change or innovation based on scientifically demonstrated evid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…The ZER model, in which a group of rural schools that maintain their autonomy as centres share an educational project, as well as travelling specialist teachers, is still in force today and coexists with some rural multigrade schools that are not grouped. It should be noted that Catalonia has a long history of innovation and research in education in general and in schools in rural contexts in particular (Tahull & Montero, 2018;Burrial, Sala, Samper & Torres-González, 2018;Ion, Díaz-Vicario & Suárez, 2021).…”
Section: Cataloniamentioning
confidence: 99%
“…The ZER model, in which a group of rural schools that maintain their autonomy as centres share an educational project, as well as travelling specialist teachers, is still in force today and coexists with some rural multigrade schools that are not grouped. It should be noted that Catalonia has a long history of innovation and research in education in general and in schools in rural contexts in particular (Tahull & Montero, 2018;Burrial, Sala, Samper & Torres-González, 2018;Ion, Díaz-Vicario & Suárez, 2021).…”
Section: Cataloniamentioning
confidence: 99%
“…Sin embargo, estas sugerencias no pueden implementarse sin una implicación decidida de políticas educativas que sitúen la investigación educativa al servicio de las escuelas, potencien la capacidad de los centros para liderar los cambios y refuercen las redes educativas del territorio, tal como lo indica la literatura sobre este tema en el ámbito nacional (Ion et al, 2021) e internacional (McGann et al, 2020;Pellegrini y Vivanet, 2020;Penuel et al, 2020). Todo ello requeriría, como mínimo, una dotación de recursos, una simplificación de los procesos de gestión, un centro de formación para el liderazgo, la incorporación de la dedicación a la investigación como tiempo de trabajo del profesorado y como requisito para el acceso a la dirección e inspección; es decir, el diseño de un Plan nacional de R+D educativa a partir de la elaboración previa de un Libro Blanco (Riera, 2019).…”
Section: Discusión Y Conclusionesunclassified
“…Teachers find it difficult to search, access and use research data without practical support (Brown, 2015;Cain, 2015), as, for example, they found the language used complex and incomprehensible for them (Murillo & Perines, 2017). Schools report problems to effective time use and spaces for interaction and collaboration, both key elements to stimulate reflection and engagement with research at the personal and school level (Ion, Díaz-Vicario, & Suárez, 2021). Also, the scientific community experiences difficulties in transferring efficiently and managing the knowledge created, generating an impact on educational practices (Ion & Castro, 2017;Lillejord & Borte, 2016), not making research accessible and understandable for teachers.…”
Section: Introductionmentioning
confidence: 99%